CE-45 Baseline factors predictive of the occurrence of neuropsychiatric damage accrual in latin american patients with systemic lupus erythematosus. (31st August 2016) - Pons-Estel, Bernardo A; Wojdyla, Daniel; Alarcón, Graciela S; Pons-Estel, Guillermo J; Ugarte-Gil, Manuel F; Caeiro, Francisco; Soriano, Enrique R; García, Mercedes A; Brenol, João C Tavares; Bonfa, Eloisa; Cavalcanti, Fernando; Vásquez, Gloria; et al.
Abstract : Background: Neuropsychiatric (NP) manifestations of systemic lupus erythematosus (SLE) are an important source of morbidity, functional impairment and poor quality of life. Several investigators have examined predictors of overall damage accrual in SLE, but predictors of NP-damage have been infrequently evaluated. The aim of this study was to assess the socio-demographic and disease related factors predictive of the occurrence of NP-damage accrual and its impact on mortality in Latin-American SLE patients with early disease. Materials and methods: We included 1100 patients from the GLADEL (G rupo L atino A mericano D e E studio del L upus) inception cohort, free of NP involvement at cohort entry (baseline) (up to 2-years of disease duration). We examined the relationship between socio-demographic characteristics, early clinical manifestations, disease activity and treatments (during the first 6 months post-baseline), with the development of NP-damage after 6 months post-baseline. NP-damage was measured with the SLICC Damage Index or Neuro-Damage (cognitive impairment or major psychosis, seizures requiring therapy for 6 months, cerebrovascular accident ever, cranial or peripheral neuropathy, transverse myelitis). We excluded from the analysis patients with neurologic involvement at entry or those who were lost to follow up before 6 months have elapsed from baseline or who had died during that time period. Data were recorded in an ARTHROS database. Statistical analysis: Patients who developed and those who did not develop NP-damage were compared using the log-rank test. Independent predictors of NP-damage accrual were identified using a Cox proportional hazard regression model. Results: During a median follow-up time of 47 months, 79 (7.2%) patients developed NP-damage. In the univariable analyses, variables predictive of NP-damage were: cardiovascular disease (4.16 per 100 patient-year of follow up [% pyf] vs. 1.62% pyf in patients without cardiovascular disease, p < 0.001), renal disease (2.92% pyf vs. 1.73% pyf, p = 0.038) and lymphopenia (2.71% pyf vs. 1.90% pyf, p = 0.012). In the multivariable analysis only cardiovascular disease (Yes vs. No) was retained in the model: HR 2.554 (95% CI: 1.580–4.128). During follow-up, mortality was higher in those who developed as compared to those who did not develop NP-damage (12/79, 15.2% vs. 34/1021, 3.3%; p < 0.0001). Conclusions: Cardiovascular disease was predictive of the occurrence of NP-damage. Furthermore, the occurrence of NP-damage was significantly associated with a higher mortality. A better control in the early stages of neurological manifestations (early diagnosis and treatment) is needed to reduce NP-damage and improve survival. Acknowledgements: On behalf of GLADEL.